A case study of rice sheath blight disease occurrence in different granary areas at Tanjong Karang, Selangor / Nur Wahidah Balqis Abdul Razak - Abdul Razak, Nur Wahidah Balqis (Faculty of Plantation and Agrotechnology, 2016)
Paddy is the most essential food crop which been cultivated worldwide. Majority of people around the world have consume the rice as the staple food for daily calorie routine intake. In Malaysia the rice cultivation as the source of income of the farmers. However, due to several attacked by major disease in rice cultivation have reduce the yield and the production thus the self-sufficiency level (SSL) set by government cannot be achieved. Sheath blight is one of the major diseases that giving harm to the rice cultivation and reportedly in Malaysia recorded a losses about 30-50%. Therefore, the objective is to study the incidence and severity of rice sheath blight and the factor contribute to the occurrence of sheath blight disease. The disease incidence and severity are effected by several factor which are fertilizer application, fungicide application, soil pH and soil type, planting method and climatic condition. A survey has been carried out at several area of Tanjong Karang in early April. A pipe 1m x 1m was used to measure placed randomly on the quadrant. All the data were observed and recorded. From the result showed that Field B has the highest average incidence and severity with 30.92% and 61.78% respectively whilst the second highest average is Field C with incidence 29.51% and severity 58.22%. The lowest average with incidence 28.03% and severity 25.98% is Field A. As for conclusion, objective of the case study are achieved and all the factor such as fertilizer application, fungicide application, soil pH and soil type, planting method and climatic condition does play a vital role in giving an impact towards the incidence and severity of sheath blight disease.